2004
DOI: 10.1161/01.res.0000141429.13560.cb
|View full text |Cite
|
Sign up to set email alerts
|

Lineage and Morphogenetic Analysis of the Cardiac Valves

Abstract: Abstract-We used a genetic lineage-labeling system to establish the material contributions of the progeny of 3 specific cell types to the cardiac valves. Thus, we labeled irreversibly the myocardial (␣MHC-Creϩ), endocardial (Tie2-Creϩ), and neural crest (Wnt1-Creϩ) cells during development and assessed their eventual contribution to the definitive valvar complexes. The leaflets and tendinous cords of the mitral and tricuspid valves, the atrioventricular fibrous continuity, and the leaflets of the outflow tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
323
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(339 citation statements)
references
References 38 publications
(59 reference statements)
13
323
0
3
Order By: Relevance
“…Both MLC-2v-Cre and ␣-MHC-Cre are expressed in the heart prior to E9 (Chen et al, 1998;de Lange et al, 2004). Despite an 85-95% reduction in cardiac Cx43 expression, cardiac-specific Cx43 CKO mice are grossly and histologically indistinguishable from their non-KO littermates and have normal ventricular function by echocardiography.…”
Section: Research Articlementioning
confidence: 99%
“…Both MLC-2v-Cre and ␣-MHC-Cre are expressed in the heart prior to E9 (Chen et al, 1998;de Lange et al, 2004). Despite an 85-95% reduction in cardiac Cx43 expression, cardiac-specific Cx43 CKO mice are grossly and histologically indistinguishable from their non-KO littermates and have normal ventricular function by echocardiography.…”
Section: Research Articlementioning
confidence: 99%
“…Further, BMP and FGF signaling pathways regulate cell lineage diversification in semilunar and AV valves (Lincoln et al, 2006a). Cell fate analysis in mice demonstrated that these diversified cell lineages arise through differentiation of valve progenitor cells present in the endocardial cushions (de Lange et al, 2004;Lincoln et al, 2004). In this study, our purpose was to examine the effects of BMP and FGF signaling on cell potential, and detailed in vitro analyses of valve progenitor cells derived from avian OFT endocardial cushions demonstrate that BMP treatment or inhibition of FGF signaling increases expression of sox9 and aggrecan associated with increased Smad1/5/8 phosphorylation, while FGF4 treatment or inhibition of BMP signaling promotes expression of scleraxis and tenascin, consistent with activated dpERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date indicate that although cells from neural crest lineages are present in both semilunar and AV valves (Nakamura et al, 2006), the majority of cells that form the cusps of the semilunar valves and the leaflets and supporting apparatus of the AV valves originate from endothelial-derived cells (de Lange et al, 2004;Lincoln et al, 2004). Endocardial cushions subsequently elongate as a result of cell proliferation, and undergo expansion and remodeling of the extracellular matrix (ECM) to form the mature semilunar and AV valves (Lincoln et al, 2004;Hinton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly our results show that in the atrioventricular canal compartment PITX2B protein is mainly present in the mural primordium of the mitral valve during heart development, suggesting a role of PITX2B in the maturation of the right portion of the atrioventricular canal. Although Liu et al, (Liu et al, 2002) speculated that Pitx2 daughter cells from myocardium invade the AV cushions and valves, in mice it has been also proposed that the leaflets and tendinous cords of the tricuspid valve are all generated from mesenchyme, derived from the endocardium with no substantial contribution from cells of the myocardial linage (de Lange et al, 2004). In whatever manner this cells arrives to the AV cushions, we cannot determine the source of cells that participate in this process since we have detected the presence of PITX2B in endocardium, myocardium and epicardium.…”
mentioning
confidence: 99%